2021
DOI: 10.3390/ijerph19010328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Consumption on Male Fertility Potential: A Narrative Review

Abstract: Alcohol abuse disorder is a serious condition, implicating more than 15 million people aged 12 years and older in 2019 in the United States. Ethanol (or ethyl alcohol) is mainly oxidized in the liver, resulting in the synthesis of acetaldehyde and acetate, which are toxic and carcinogenic metabolites, as well as in the generation of a reductive cellular environment. Moreover, ethanol can interact with lipids, generating fatty acid ethyl esters and phosphatidylethanol, which interfere with physiological cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 143 publications
2
24
0
Order By: Relevance
“…The question that arises is how the systemic state, such as proven lifestyle factors such as excessive alcohol use and smoking, influences male infertility [ 33 , 34 ]. Excessive alcohol consumption is reported to increase OS within the testis as a result of a significant reduction in testosterone, an increase in serum lipid peroxidation byproducts, and a decrease in antioxidants [ 35 ]. However, no study to date has directly examined the link between several lifestyle and environmental factors and local oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The question that arises is how the systemic state, such as proven lifestyle factors such as excessive alcohol use and smoking, influences male infertility [ 33 , 34 ]. Excessive alcohol consumption is reported to increase OS within the testis as a result of a significant reduction in testosterone, an increase in serum lipid peroxidation byproducts, and a decrease in antioxidants [ 35 ]. However, no study to date has directly examined the link between several lifestyle and environmental factors and local oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that ethanol-induced reproductive toxicity may be related to the excessive production of ROS and lipid peroxidation products [23]. MDA is a terminal metabolite produced by free radicals attacking cell membranes, a process known as lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature review of published studies on infertility (up to 31 May 2022) to identify risk factors for infertility. To be more specific, 3 obesity-related traits (BMI, body fat percentage, waist-to-hip ratio, waist-to-hip ratio adjusted for BMI) [ 5 , 6 , 14 ], 16 lifestyle and dietary factors (education [ 15 ], smoking [ 8 ], drinking [ 16 , 17 ], coffee intake [ 18 , 19 ], sleep duration [ 20 , 21 ], insomnia [ 22 ], physical activity [ 5 , 23 ], sedentary behavior [ 24 ], serum 25-Hydroxyvitamin D levels [ 25 ], zinc [ 26 ], omega-6 fatty acids, omega-3 fatty acids [ 27 , 28 ], total fatty acids, saturated fatty acids, polyunsaturated fatty acids, monounsaturated fatty acids [ 29 , 30 ]), and 2 biochemical measures (HDL, LDL) were considered as underlying risk factors and were included in a two-sample MR analysis as an exploratory analysis. Table 2 provides details on modifiable risk factors.…”
Section: Methodsmentioning
confidence: 99%